If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-6x=-7x+2
We move all terms to the left:
4-6x-(-7x+2)=0
We get rid of parentheses
-6x+7x-2+4=0
We add all the numbers together, and all the variables
x+2=0
We move all terms containing x to the left, all other terms to the right
x=-2
| -1=x/2+2 | | 81-9a²=0 | | 5(5x-3)+8=-6 | | 14=3.5(4z-8) | | -2=-1+k/14 | | (x+7)^2+11×(x+7)+28=0 | | 12y-4(1+y)=2(2y-2)-20 | | -p/5=-4 | | 16+9w=4-w | | 9x+2=-8+6x+16 | | 21-8x=7x | | 3y2=504 | | -5/6=-1/6v | | 2a+3a+6=21 | | 6x+11=68 | | 1-3x(8x-4)=1 | | 17-2x=-5x+5 | | 5−3⋅(3+5x)=71 | | 2x/3-x/6=x/4+1 | | 2x+6777=34 | | =−8+u4 | | =−8+u+4 | | 10+x=9 | | 5/2=154/x | | 9f+16=-26 | | 9=5+4z | | -8(1-2p)+2p=5p+5 | | x/3-1=3+x/2 | | 4n+10=4 | | 3(5f+5)=3(6f-5) | | 13x-15=14-12x | | 65-2x=23x |